2015
DOI: 10.1016/j.chom.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Individual Members of the Microbiota Disproportionately Modulate Host Innate Immune Responses

Abstract: Summary Predicting host health status based on microbial community structure is a major goal of microbiome research. An implicit assumption of microbiome profiling for diagnostic purposes is that the proportional representation of different taxa determine host phenotypes. To test this assumption, we colonized gnotobiotic zebrafish with zebrafish-derived bacterial isolates and measured bacterial abundance and host neutrophil responses. Surprisingly, combinations of bacteria elicited immune responses that do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
174
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(185 citation statements)
references
References 34 publications
10
174
1
Order By: Relevance
“…Consistent with the keystone-pathogen concept, a recent study on the intestinal innate immune response of gnotobiotic zebrafish showed that combinations of distinct bacterial species induce immune responses that do not reflect the numerically dominant species [43]. Rather, different species exert different ‘per capita’ immunostimulatory effects, suggesting that knowledge of specific properties of individual species may provide predictive insights into the function of multi-species communities [43].…”
Section: Master Manipulators: Keystone Pathogensmentioning
confidence: 96%
See 2 more Smart Citations
“…Consistent with the keystone-pathogen concept, a recent study on the intestinal innate immune response of gnotobiotic zebrafish showed that combinations of distinct bacterial species induce immune responses that do not reflect the numerically dominant species [43]. Rather, different species exert different ‘per capita’ immunostimulatory effects, suggesting that knowledge of specific properties of individual species may provide predictive insights into the function of multi-species communities [43].…”
Section: Master Manipulators: Keystone Pathogensmentioning
confidence: 96%
“…Rather, different species exert different ‘per capita’ immunostimulatory effects, suggesting that knowledge of specific properties of individual species may provide predictive insights into the function of multi-species communities [43]. Moreover, the fact that minor members can exert dominant effects challenges the Occam’s razor interpretation (which is inherent in compositional analyses) that the relative abundances of different taxa or species can have predictive value for pathology.…”
Section: Master Manipulators: Keystone Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Each microbial response may impact the host, and host feedbacks can mitigate or exacerbate changes in the microbial community. 19 However, vignette examples may be misleading, as the true complexity of a gut microbiome has never been exhaustively quantified. Thus, it remains an outstanding challenge to reverse engineer the interaction networks that characterize community microbiome-host effects relative to host interactions with a single bacterial species.…”
Section: Introductionmentioning
confidence: 99%
“…33 Although apparently contradictory, the diversity of the gut microbiome could include some species of bacteria as suppressive while others could function to stimulate an immune inflammatory response. 34 Rutkowski and colleagues did not find a significant difference in the quantity of PD-1 between Tlr5-/- and wild-type mice models, however, it could be of further interest to measure responses to anti-CTLA-4 Ab. Even more intriguingly, the functional role of TLR-5 immunosuppressive bacteria might be useful for research regarding the efficacy of immunosuppressive drugs such as anti-CD3 mAb, or teplizumab, supported by preliminary investigations focusing on the synergistic functionality between gut commensal bacteria and immunosuppressive drugs.…”
mentioning
confidence: 99%